Platinum and taxane chemoresistance mechanisms in ovarian cancer cells - Busschots, Steven (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2015)
Ovarian cancer is the leading cause of death from a gynaecological malignancy, typically presenting at late stage due to difficult diagnosis and lack of suitable screening tools. The standard treatment of combination taxol/carboplatin chemotherapy often fails and patients relapse with chemoresistant disease. Patients have a median survival of two years following recurrence and will all eventually die from their disease. Patients with BRCA1 deficiencies have an increased lifetime risk of approx. 39-46% for developing ovarian cancer.
Keywords: Histopathology and Morbid Anatomy, Ph.D.; Ph.D. Trinity College Dublin